The Role of Computer-Assisted Navigation in Total Knee Arthroplasty Outcomes: A Systematic Literature Review - Agusta, Martin (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The increasing use of Total Knee Arthroplasty (TKA) to treat severe osteoarthritis demands high surgical precision to ensure optimal alignment, reduce complications, and improve implant longevity. Computer-Assisted Navigation (CAN) has emerged as a technological solution to enhance accuracy in TKA; however, its long-term clinical effectiveness remains debated. This study aims to systematically assess whether CAN significantly improves TKA outcomes compared to conventional methods. Using PRISMA and Cochrane Collaboration guidelines, a systematic literature review was conducted involving 19 eligible peer-reviewed studies published between 2014 and 2024, retrieved from Scopus, PubMed, and Crossref. Data were analyzed using a narrative synthesis approach. Findings indicate that CAN improves radiological alignment and reduces certain complications, including soft tissue damage and inflammatory responses. However, evidence regarding its impact on functional outcomes, patient satisfaction, and revision rates remains inconclusive. Although some studies reported better postoperative range of motion and marginal increases in patient satisfaction, others found no significant difference. These mixed results highlight the need for further longitudinal and randomized studies. The study underscores CAN’s potential in improving surgical accuracy, while urging continued research to validate its broader clinical and economic value.